The moderating role of gender on the relationship between childhood attention deficit and hyperactivity symptoms and functional impairment - Zehra Koyuncu; Kübra Aslantürk Halil; Özge Selçukoğlu Kilimci; Büşra Arslan; Ezgi Tanrıöver Aydın; Emine Yücel; Yekta Uğur Arvas; Nazan Ebru Aksu; Cana Aksoy Poyraz; Ömer Faruk Demirel; Leyla Küçük; Burak Doğangün; et al. (PLoS ONE, 2025)
This study aimed to examine the link between childhood attention deficit and hyperactivity symptoms (CAS) and functional impairment in university students, while also investigating whether gender moderates this relationship. Six hundred and eighty university students participated in this cross-sectional study. The assessment was conducted using the Wender–Utah Rating Scale-25 (WURS), the Brief Symptom Inventory (BSI), and the Weiss Functional Impairment Rating Scale – Self Report (WFIRS-S). The relationship between CAS and general and domain-based functional impairment was evaluated using eight moderation models. Control variables, including age and concomitant psychiatric symptoms (five BSI scores), were added to the models. We observed positive associations between WURS and all WFIRS-S scores. In addition, WURS significantly interacted with gender in explaining WFIRS-S total (t = –2.26, p =.024). Gender also moderated the link between WURS and impairments in social (t = –2.00, p =.046) and risk domains (t = –2.86, p =.004). Accordingly, the associations between CAS and overall functional impairment, as well as impairments in social and risk domains, were stronger in men than in women. These findings highlight the significant role of CAS in functional impairments among university students, with gender emerging as a key moderating factor, particularly in social and risk-related domains.